Inverse stable isotope probing–metabolomics (InverSIP) identifies an iron acquisition system in a methane-oxidizing bacterial community - Jose Miguel D. Robes; Tashi C. E. Liebergesell; Delaney G. Beals; Xinhui Yu; William J. Brazelton; Aaron W. Puri (Proceedings of the National Academy of Sciences, 2025)
Methane is a potent greenhouse gas and a target for near-term climate change mitigation. In many natural ecosystems, methane is sequestered by microbial communities, yet little is known about how constituents of methane-oxidizing communities interact with each other and their environment. This lack of mechanistic understanding is a common issue for many important microbial communities, but it is difficult to draw links between available sequencing information and the metabolites that govern community interactions. Here, we develop and apply a technique called inverse stable isotope probing–metabolomics (InverSIP) to bridge the gap between metagenomic and metabolomic information and functionally characterize interactions in a complex methane-oxidizing community. Using InverSIP, we link a highly transcribed biosynthetic gene cluster in the community with its secondary metabolite product: methylocystabactin, a triscatecholate siderophore not previously observed in nature. We find that production of methylocystabactin is widespread among methanotrophic alphaproteobacteria and that it can be used by another methanotroph in the community that does not produce this siderophore itself. Functional assays reveal that methylocystabactin supports methanotroph growth and the activity of the methane-oxidizing enzyme soluble methane monooxygenase under conditions where bioavailable iron is limited, establishing an important molecular link between methane-oxidation and the insoluble iron found in many natural environments. These findings contribute to a molecular-level understanding of these environmentally important bacterial communities and establish InverSIP as a broadly applicable genomics-guided strategy for characterizing metabolites in microbial ecosystems.